ELEMENTAL ANALYSIS OF AYURVEDIC DRUGS (BHASMAS) BY ATOMIC ABSORPTION SPECTROMETER - A, ASHWINI; BR, KERUR (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: Ayurvedic drugs/bhasmas are very potent and promising drugs for the treatment of various ailments. Bhasmas are the multielement samples, and the present work deals the analysis of the concentration of metallic elements in three ayurvedic bhasmas of four different brands, to compare and know the quality of commercial bhasma in market. Methods: Commercially available abhraka bhasma (AB), mandoor bhasma (MB), and godanti bhasma (GB) in market from four different manufacturing companies were procured, and bhasma sample solution was prepared to analyze the elemental concentrations in bhasma; the solution is subjected to flame atomic absorption spectrometer (FAAS) technique and determined elemental concentration in bhasmas of four different commercial brands. Results: FAAS analysis explores the presence of Mg, Al, K, Ca, Cr, Mn, Fe, Cu, Zn, Mo, and Cd elements’ concentration in three bhasmas/drugs by four manufacturers. AB is rich in Al and Fe following the other elements in low concentrations, MB is rich in Fe, Ca, Mn, Cu, K, and Al and other elements are present in less quantity, and GB is rich in Ca and all other elements were very less in quantity. Conclusion: FAAS analysis showed that there is a difference in quantity/concentration of elements present in bhasma, aluminum (Al) is found high in Patanjali brand bhasmas compared to other three brands, and the toxic metal cadmium (Cd) is found in Dhootapapeshwar mandoor bhasma (DMB) (0.0458 mg/l), except DMB, all bhasmas found free from toxic metals, which reveal that there is a variation in quality of bhasmas from different manufacturers, and the elements present in bhasmas are found to be in permissible range for human intakes. As the mineral elements are essential in human diet, if the amount of any elements becomes too high in body, then it can affect the functioning of other important minerals in body causing the severe health problems, so it is must, to balance all nutrients in human diet, either through food or medicines. Hence, the present analysis work focuses on the variation of concentrations of elements present in bhasma of different manufacturers, which will help in practitioners to compare and refer good quality bhasmas or drugs in terms of their ingredients/elements, which plays a major role in functioning of human body normally. Further work is necessary to carry out on bhasmas and ayurvedic formulations in order to get good of diet supplementation.